Characterization of [3H]desipramine binding associated with neuronal norepinephrine uptake sites in rat brain membranes - Lee, CM (J Neurosci, 1982)
A variety of evidence indicates that [3H]desipramine can label neuronal norepinephrine uptake sites in brain membranes. Pretreatment of rat cerebral cortical membranes with 0.3 M KCl increases the ratio of high affinity to low affinity saturable [3H]desipramine binding. With this improved tissue preparation, we have confirmed our earlier observation that the high affinity [3H]desipramine binding component (KD = 2 to 4 nM) is associated with norepinephrine neuronal uptake sites. The potencies of various antidepressant drugs in reducing [3H]desipramine binding correlate with their inhibition of neuronal [3H]norepinephrine accumulation. Like the norepinephrine uptake system, high affinity [3H]desipramine binding is dependent both on sodium and chloride, with half-maximal stimulation by 10 mM chloride. Although bromide can substitute for chloride to stimulate binding, other anions, including iodide, fluoride, acetate, citrate, and phosphate, are inactive. Comparable sodium and anion regulation of [3H]imipramine binding to serotonin uptake recognition sites also is observed. The association of [3H]desipramine binding sites with neuronal norepinephrine uptake sites is supported further by the selective abolition of high affinity [3H]desipramine binding following the destruction of central norepinephrine neurons by intraperitoneal administration of DSP-4 (N-(2- chloroethyl)-N-ethyl-2-bromobenzylamine). In vitro incubation of cerebral cortical membranes with DSP-4 also selectively abolishes the high affinity [3H]desipramine binding, an effect which cannot be reversed by repeated washing of the membranes, suggesting that DSP-4 alkylates neuronal norepinephrine uptake sites.